Polymer Melt Flow Progression In Confined Geometries And Its Connection With Product Reliability - Law, Yeong Shyang (Universiti Sains Malaysia, 2017)
The progression of melt flow in confined geometries has been carried out in this investigation. The PMMA has been selected due to its characteristic which has high transparency. The dumbbell shape is used as the confined geometry and it is drawn using Solidwork 2013. The polymer melt flow of PMMA is used Cadmould software to undergo simulation. Three different type of processing parameters are carried out optimized and using design expert under general factorial method. Three manipulated parameter that have been introduced: melt temperature, injection pressure and mould temperature. On the other hand, three types of experiment are implanted to determine the product reliability. The birefringence test is carried out to determine the residual stress inside geometry. Heat reversion test is carried out to investigate the internal residual stress via shrinkage. Next, the dynamic bending is carried out to analyze their relationship of the product reliability and polymer melt flow. It is found that both approaching agreed higher processing parameter beyond the degradation of polymer melt, the higher the strength properties of the polymer material.